PTU-069 Antiplatelet versus anticoagulant effects in non-variceal upper gastrointestinal bleeding. (June 2019) - Taha, Ali; McCloskey, Caroline; Craigen, Theresa; Angerson, Wilson
Abstract : Introduction: Non-variceal upper gastrointestinal bleeding (NVUGIB) typically originates from mucosal damage or ulceration. The situation can be complicated by the wide use of antiplatelet agents (APs) and anticoagulants (ACs). These drugs, e.g. aspirin, may directly cause ulcers or they may provoke bleeding or re-bleeding. We aimed to assess the individual impacts of AP vs. AC activities on the clinical outcomes of NVUGIB. Methods: Patients with NVUGIB were sub-grouped according to their use of APs, ACs, or none (controls). They were excluded if they had portal hypertension or used NSAIDs. APs included aspirin, clopidogrel, ticagrelor, and dipyridamole. ACs included warfarin, heparin, and apixaban. A composite endoscopy score was devised. Clinical details were recorded including Blatchford score, admission, blood transfusion, re-bleeding, and 30-day mortality. The Kruskal-Wallis or chi squared tests were used as appropriate. Odds ratios (ORs), comparing outcomes in AP and AC patients with controls, were calculated and adjusted for age, sex and endoscopy score using logistic regression. Results: The details of patients with NVUGIB (N=3233) including users of APs, ACs, and controls, who presented 2005–2016, are shown in table 1 . The AP and AC groups were older and had worse clinical outcomes than controls. When ORs were adjusted for age, sex and endoscopy score, APs and ACs were still more likely to be admitted [APs: OR (95% CI), 1.38 (1.10–1.74), P=0.006; ACs: 3.48 (2.01–6.02), P<0.001], and transfused [APs: 1.38 (1.15–1.66), P=0.001; ACs: 2.53 (1.87–3.43), P<0.001]. However, re-bleeding remained significant only in ACs [2.26 (1.58–3.25), P<0.001], and neither APs nor ACs had increased mortality [APs: 0.75 (0.50–1.12), P=0.16; ACs: 1.00 (0.53–1.88), P=1.00]. Conclusions: In NVUGIB, the antiplatelet and anticoagulant activities are associated with older age and greater need for admission, transfusion, and re-bleeding. These outcomes were more marked in users of anticoagulants even after adjustment for age, sex, and endoscopy, but with insignificant effect on mortality.